International business - Griffin, Ricky W.; Pustay, Michael W. (Pearson, 2013)
"International Business" illustrates how successful managers must function in a competitive world. Packed with current examples that reflect the vibrancy of the international business field, this reader-friendly text offers a managerial approach that keeps an emphasis on skills development, emerging markets and geographical literacy